RANCANG BANGUN SISTEM WAYFINDER HOSPITAL DI RUMAH SAKIT UMUM DR. SAIFUL ANWAR MALANG - Jerico Elvan Santoso; Winarto Eko Wahyono; Vinno Christmantara (Universitas Katolik Widya Karya Malang, 2023)
General Hospital Dr. Saiful Anwar Malang is the largest hospital in the Malang area which has a building with wide coverage, with frequent changes in poly rooms that change location. From the observations of the author, there are problems often encountered by visiting families or visitors who have difficulty finding the location of the patient's room. The wayfinder system is a system proposed by the author to overcome this problem. This system is designed using a display that is easy for visitors or visitors to use on a website basis and it is possible to update routes if there is a room change again. The results of this study are in the form of a wayfinder system that can be easily used to determine room locations so that hospital services become more efficient and look professional.